Analysis of Promoter Hypermethylation of DAPK and BAX Apoptotic Genes in Iranian Gastric Cancer Patients Undergoing Chemotherapy - Somayeh Nazerian Poudineh (Middle East Journal of Cancer, 2020)
Background: The apoptotic route is mostly damaged in gastric cancer tumor cells. DNA methylation of promoter associated CpG islands inactivates tumor suppressor genes. The objective of the present study was to analyze the hypermethylation of death-associated protein kinase (DAPK) and Bcl-2-associated X protein (BAX) genes in individuals suffering from gastric cancer and undergoing chemotherapy. Methods: Genomic DNA was extracted from blood samples and the tissue fixed in the paraffin of 30 patients and normal individuals. Hypermethylation investigation of DAPK and BAX genes was conducted via methylation specific PCR technique, the outcomes of which were analyzed through electrophoresis and SPSS software version 20. Results: Methylation of both BAX and DAPK genes with a frequency of (28.3%, 21.7%) in blood and (23.3%, 23.3%) in tissue, respectively, had a significant relationship with gastric cancer (P˂0.01). A significant relationship was also observed between the methylation of BAX gene in tissue and tumor type (12, 35.3% and P˂0.01). No relationship was found between methylation and grade, stage, node, age, sex, and other pathologic and clinical data of the patients (P>0.05). There was a significant association between simultaneous methylation of DAPK and BAX genes in tumor and typical tissues with methylation a frequency of 40% and 95.83%, respectively (P˂ 0.01). Conclusion: Methylation of the BAX and DAPK genes can be used as a biomarker in bloodand an approach in the early detection of malignity and illness management. Methylation inhibitors with the potential for drug targeting of DAPK and BAX can further be employed in pharmacotherapy.